Decarbonizing Tourism: The Impact of Renewable Energy in the World’s Most Tourism Intense Countries - Djalilov, Bekhzod; Yarkulova, Marifat; Yarasheva, Vasila; Shadieva, Dildora; Tosheva, Shakhnoza; Abduvalieva, Mumtozkhon (International Journal of Energy Economics and Policy, 2025)
This study investigates the dynamic relationship between tourism, renewable energy consumption, and CO2 emissions in the top 50 tourism-intensive countries, measured by the share of tourism receipts in total exports. Using panel data from 2000 to 2020, the analysis applies a two-step system GMM estimator to address endogeneity concerns, along with fixed effects and quantile regression techniques. The findings reveal that while tourism contributes to increased CO2 emissions, renewable energy consumption plays a significant mitigating role. Specifically, a 1% increase in renewable energy use is associated with a 1.1% reduction in CO2 emissions, with the strongest effects observed in high-emission countries. The study also finds empirical support for the Environmental Kuznets Curve (EKC) hypothesis, with a calculated turning point at approximately USD 5,420 GDP per capita. By focusing on tourism-driven economies, this research makes several novel contributions: It highlights the environmental risks posed by tourism, underscores the importance of renewable energy in achieving sustainable development, and offers policy-relevant insights for balancing economic growth with environmental preservation. The results suggest that integrating renewable energy strategies into tourism planning is essential for reducing the sector’s carbon footprint without compromising growth.